2000
DOI: 10.1017/s0003598x00059846
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoindian artefact distributions: evidence and implications

Abstract: The distribution of projectile points over broad geographic areas yields important insights about Palaeoindian settlement pattern and history. While traditionally viewed as a Great Plains adaptation, the data show that fluted points are far more common in Eastern North America. These artefacts are not evenly spread across the landscape, furthermore, but occur in distinct concentrations. Within some of these areas distinct cultural traditions quickly emerged, something that appears tied to the sudden onset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…These data are evidence that humans were present on the Northern Channel Islands when contemporary Paleoindian peoples were well distributed throughout North America and used a wide diversity of available resources including the hunting of large game animals with Clovis spear points (Haynes, 2005;Waters and Stafford, 2007). Clovis points and related technology, although found on the adjacent mainland and throughout much of North America (Anderson and Faught, 2000;Erlandson et al, 2007;Rondeau et al, 2007), have not been found on the Northern Channel Islands, but the potential overlap between the most recently dated M. exilis skeleton and the Arlington skeletal material suggests that humans may well have encountered these animals at this early date. Regardless, early human presence on these islands provides unequivocal evidence for seaworthy boats and sufficient skill to safely navigate the Santa Barbara Channel ).…”
Section: Late Quaternary Archaeological Recordsmentioning
confidence: 88%
“…These data are evidence that humans were present on the Northern Channel Islands when contemporary Paleoindian peoples were well distributed throughout North America and used a wide diversity of available resources including the hunting of large game animals with Clovis spear points (Haynes, 2005;Waters and Stafford, 2007). Clovis points and related technology, although found on the adjacent mainland and throughout much of North America (Anderson and Faught, 2000;Erlandson et al, 2007;Rondeau et al, 2007), have not been found on the Northern Channel Islands, but the potential overlap between the most recently dated M. exilis skeleton and the Arlington skeletal material suggests that humans may well have encountered these animals at this early date. Regardless, early human presence on these islands provides unequivocal evidence for seaworthy boats and sufficient skill to safely navigate the Santa Barbara Channel ).…”
Section: Late Quaternary Archaeological Recordsmentioning
confidence: 88%
“…The impact-related effects would have been devastating for animals and plants. For humans, major adaptive shifts are evident at 12.9 ka, along with an inferred population decline, as subsistence strategies changed because of dramatic ecological change and the extinction, reduction, and displacement of key prey species (55,56). Many sites indicate that both Clovis people and extinct megafauna were present immediately before the YD event, but, except in rare cases, neither appears in the geologic record afterward.…”
Section: Discussionmentioning
confidence: 99%
“…For example, was there selection for new weapon-delivery systems that had to do with changing environments and thus changes in available game animals at the end of the Pleistocene? How much social interaction was there among terminal Pleistocene and early Holocene groups in the southeastern United States (Anderson, 1991;Anderson & Faught, 2000;Anderson & Gillam, 2000;Morrow & Morrow, 1999)? At base, these are all historical questions, and cladistics offers a means of framing phylogenetic hypotheses.…”
Section: Resultsmentioning
confidence: 99%